2021
DOI: 10.1007/s12144-021-01724-5
|View full text |Cite
|
Sign up to set email alerts
|

How are OCD patients and their families coping with the COVID-19 pandemic? A qualitative study

Abstract: Patients with obsessive-compulsive disorder (OCD) are likely to be affected by the COVID-19 crisis since fear of contamination is highly prevalent in this illness and disease reminders are omnipresent during this crisis. The current study aimed to investigate the impact of the pandemic and the lockdown on the mental health, well-being and coping abilities of OCD patients and their families in order to increase our understanding of the underlying mechanisms of the disorder. Twenty-two patients and 13 family mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 46 publications
3
9
0
1
Order By: Relevance
“…Online studies of people who self-identified as having OCD showed a similarly large range of outcomes, with between 33% and 76% of samples reporting symptom worsening ( Jelinek et al, 2021 ; Littman et al, 2020 ; Wheaton et al, 2021 ). However, Tandt et al (2021) found that after an initial worsening of symptoms, individuals with OCD subsequently experienced symptom improvement, and others found that children ( Schwartz-Lifshitz et al, 2021 ) and some adults ( Littman et al, 2020 ) reported improved functioning months into lockdown.…”
mentioning
confidence: 99%
“…Online studies of people who self-identified as having OCD showed a similarly large range of outcomes, with between 33% and 76% of samples reporting symptom worsening ( Jelinek et al, 2021 ; Littman et al, 2020 ; Wheaton et al, 2021 ). However, Tandt et al (2021) found that after an initial worsening of symptoms, individuals with OCD subsequently experienced symptom improvement, and others found that children ( Schwartz-Lifshitz et al, 2021 ) and some adults ( Littman et al, 2020 ) reported improved functioning months into lockdown.…”
mentioning
confidence: 99%
“…The media guidelines for preventing COVID-19 infection are in line with the obsessions of people with OCD, but contradict the treatment of obsessive-compulsive disorder. In times of pandemic, there is a difficulty between distinguishing standard disinfection techniques and dysfunctional obsessive-compulsive behavior [22]. Researchers became interested in the impact of the pandemic on the course of obsessive compulsive disorder and its prognosis [27].…”
Section: Discussionmentioning
confidence: 99%
“…Lockdown system or situation during the COVID-19 [3,6,18,26,29,[35][36][37][38][39][40][41], impairment to social and occupational functioning [9] Restricted situation Social consequences of COVID-19 [3], restrictions [35], physical distancing and self-isolation [36], isolation [29,42], reduced social opportunities [42], social restriction [38], isolation and loneliness/reduced contact with key individuals/ living alone/cessation or reduction of service (including absence of face to face support) [16], limited/restricted [43], social distancing [6,18,29,40,43], losing direct social and physical contact [9], restricted in a situation [44] Uncertain future…”
Section: Lockdown Systemmentioning
confidence: 99%
“…Increased suicide Suicide ideation [3,6], self-harm [15,16], risk factors of suicide [9,14,15,18], suicide [6,29,35,37,42,44], suicidal intent and behavior [47], suicidality [46], suicidal actions and ambivalent to living or dying [6] Decreased mental health Decreased mental health problem [3,16,29,44], feeling isolated and the specific mirroring of abuse [38], foster neglect and abuse [40] Decreased well-being Decreased well-being [3,29], negative wellbeing [36], affect their care and wellbeing [40] (1) Out of control The situation during the COVID-19 pandemic is out of control; an individual's ability to control impulses and modify inappropriate emotions and thoughts [48,49] and the world is desperately exhausted [48]. Out of control is.…”
Section: Consequencesmentioning
confidence: 99%